1994
DOI: 10.1007/bf02047214
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of C-reactive protein in acute appendicitis

Abstract: Serum C-reactive protein was measured in 56 patients hospitalized with a suspected diagnosis of acute appendicitis. Based on these determinations, four groups of patients were defined: Group A = 26 patients with acute appendicitis who had a C-reactive protein level higher than 2.5 mg/dl. Group B = 4 patients with a C-reactive protein level lower than 2.5 mg/dl who, after surgery based on a presumed diagnosis of acute appendicitis, were found to have a normal appendix. Group C = 22 patients with nonspecific abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 5 publications
0
36
0
3
Order By: Relevance
“…The diagnostic value of CRP and WBC has been established in patients with appendicitis [11,25,[27][28][29][30][31][32]. It has been demonstrated that CRP could differentiate between children with non-perforated from children with perforated appendicitis [25]; this observation has also been reported in adults [28,32].…”
Section: Laboratory Tests: Wbc and Crpmentioning
confidence: 69%
“…The diagnostic value of CRP and WBC has been established in patients with appendicitis [11,25,[27][28][29][30][31][32]. It has been demonstrated that CRP could differentiate between children with non-perforated from children with perforated appendicitis [25]; this observation has also been reported in adults [28,32].…”
Section: Laboratory Tests: Wbc and Crpmentioning
confidence: 69%
“…Albu et al evaluated level of CRP in cases of AA and reported that sensitivity and specificity were 100% and 84.6%, respectively, when cut-off value was 2.5 mg/dL. [12] In study performed by Mengücük et al, CRP level of patients with pathological diagnosis of appendicitis (focal, suppurative, or perforated) was statistically significantly higher when compared with cases that did not have pathological diagnosis of appendicitis. [13] In another study conducted by Sack et al, CRP level of group with PA and group with abdominal pain who did not undergo surgery was compared.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, if the C-reactive protein level in blood drawn 12 hours after the onset of symptoms is less than 2.5 mg/dL, acute appendicitis can be excluded. 6 The triple test (WBC count, CRP and Neutrophil percentage) is recommended as a help in reducing the significant rate of negative laparotomies in patients suspected of having acute appendicitis. 7 We found that elevated serum CRP levels support surgeon's clinical diagnosis.…”
Section: Review Of Literaturementioning
confidence: 99%